Evaluation of physicochemical, functional and microbiological properties of naturally fermented EVIARC sweet jackfruit (Artocarpus heterophyllus Lam.) seeds flour - Cuadra, Maria Norfrelij J.; Galvez, Lorina A.; Amestoso, Felix J. (Annals of Tropical Research, 2018)
Jackfruit seeds are rich in carbohydrates and protein. It can be processed into flour as a nutritious product which can be stored for future use. However, jackfruit seed flour has limited cooking applications, thus, the need to improve its functionality through natural fermentation process. The study was conducted to determine the effects of lactic acid and fermentation time on the physicochemical, functional and microbiological properties of the fermented jackfruit seed flour, compared to its unfermented counterpart. A 3×3 full factorial design following Completely Randomized Design (CRD) with different levels of lactic acid (0, 1.5, 3%) and fermentation time (16, 24, 32 hours) and with a control treatment was used. Data for all experimental combinations were analyzed using One-way ANOVA where means were compared using Tukey’s HSD. Analysis of variance results revealed that the physico-chemical and functional properties of control treatment is significantly different from the fermented jackfruit flour in terms of pH, moisture and carbohydrates. Moreover, fermentation and lactic acid contributed to increase in quality values of the jackfruit flour except for %energy, %carbohydrates and bulk density. The faster drop in pH brought about by lactic acid increased the count of aerobic bacterial, lactic acid bacteria, yeasts and molds.